Effects of a shoulder injury prevention strength training program on eccentric external rotator muscle strength and glenohumeral joint imbalance in female overhead activity athletes - Niederbracht, Y.; Shim, A. L.; Sloniger, M. A.; Paternostro-Bayles, M.; Short, T. H. (The Journal of Strength and Conditioning Research, 2008)
Imbalance of the eccentrically-activated external rotator cuff muscles versus the concentrically-activated internal rotator cuff muscles is a primary risk factor for glenohumeral joint injuries in overhead activity athletes. Nonisokinetic dynamometer based strength training studies, however, have focused exclusively on resulting concentric instead of applicable eccentric strength gains of the external rotator cuff muscles. Furthermore, previous strength training studies did not result in a reduction in glenoumeral joint muscle imbalance, thereby suggesting that currently used shoulder strength training programs do not effectively reduce the risk of shoulder injury to the overhead activity athlete. Two collegiate women tennis teams, consisting of 12 women, participated in this study throughout their preseason training. One team (n = 6) participated in a 5-week, 4 times a week, external shoulder rotator muscle strength training program next to their preseason tennis training. The other team (n = 6) participated in a comparable preseason tennis training program, but did not conduct any upper body strength training. Effects of this strength training program were evaluated by comparing pre- and posttraining data of 5 maximal eccentric external immediately followed by concentric internal contractions on a Kin-Com isokinetic dynamometer (Chattecx Corp., Hixson, Tennessee). Overall, the shoulder strength training program significantly increased eccentric external total work without significant effects on concentric internal total work, concentric internal mean peak force, or eccentric external mean peak force. In conclusion, by increasing the eccentric external total exercise capacity without a subsequent increase in the concentric internal total exercise capacity, this strength training program potentially decreases shoulder rotator muscle imbalances and the risk for shoulder injuries to overhead activity athletes.